Investigation of the possible anti-diabetic activity of Icacina trichantha, Ananas cosmos and Uraria picta in a rat model - Fatokun, Femi Kayode (My University, 2011)
Natural remedies from medicinal plants are considered to be effective and safe alternative treatment for diabetes mellitus. The aim of this study was to demonstrate the hypoglycaemic and antidiabetic activity of the aqueous extract of Icacina tracantha (tuber) (fam Icacinaceae)Ananas cosmos (fam. Bromeliaceae)and Uraria picta (leaves) (fam leguminosae) on an animal model of insulin resistance, a condition which predisposes to type 2 diabetes. The plants have a long history of use as anti-diabetic agents in western Nigeria. Method: 120 male Sprague-Dawley rats were assigned into two major groups. One group was fed on normal rat chow with the other group fed on a high calorie diet for four months a period sufficient for the animals to be fed to attain insulin resistance. The animals were then randomly assigned into different groups (each containing 6 male rats). The plant crude extracts were made by weighing specific dried quantities of each plant, boiling in distilled water for about 2 hours, cooling overnight and separating solid from liquid by filtration. The solution was then poured into preweighed 250 ml beakers and allowed to dry in an oven at a temperature of 60oC. The dried, crude extracts were then weighed out and required doses prepared from the extracts. A non-treated group of animals was used as the control. The mixed dose of extract was administered at 300 mg/kg. Over a 3 week period, all the animals were orally dosed with the different doses of plant extracts daily while metformin was administered through the animals’ drinking water, blood was collected from the tail vein of each rat prior to dosing and thereafter weekly, plasma was preserved and 6 analysed for glucose, insulin, free fatty acid concentrations and calculation of HOMA values to determine insulin sensitivity. During this period, the animals were weighed weekly and food intake was measured every three days. An oral glucose tolerance test (OGTT) was performed after the dosing period and fasting, 0, 30, 60 and 120 minute blood samples were taken and assayed for glucose concentration. Animals were terminated and blood analysed. Statistical analysis: The results were tabulated as mean ± standard deviation and percentage median ± quartile range. The statistical analysis for other parameters was carried out via ANOVA (between groups) and Student’s paired T test (within groups). Only data from percentage median and quartile range was used because of the observed variation in glucose concentration between groups even at baseline values. Statistica software (StatSoft, Tulsa, OK, USA) was used for the analysis. Results: All plant extracts in the study showed differing concentration of significant difference in their effect on the plasma glucose, insulin and free fatty acid concentrations in the rat. The most significant effect was observed on the insulin concentration in the normal rat chow and high calorie diet fed animals. The plant extracts were observed to improve insulin sensitivity in most of the groups. This effect was more significant in the normal rat chow fed rats. The effect of the plant extracts on the weight, food consumed glucose and free fatty acid was minimal and in most of the groups was not significant. Conclusion: In conclusion, the results obtained suggest that the plant extracts may be used to improve insulin resistance in the management of diabetes mellitus.
MSc Pharmacology, Faculty of Health Sciences, University of the Witwatersrand
Keywords: plants; diabetes; insulin resistance